2016
DOI: 10.1021/acscatal.6b02551
|View full text |Cite
|
Sign up to set email alerts
|

Delineating The Multiple Roles of B(C6F5)3 in the Chemoselective Deoxygenation of Unsaturated Polyols

Abstract: A set of B­(C6F5)3-catalyzed methods for diversification of unsaturated carbohydrate derived substrates is disclosed. Lewis acid cyclization, allylic alcohol hydrosilylation, and selective silyl group exchange is achieved with this single versatile catalyst. Allylic polyols and highly enriched (Z)-triols are obtained in high yields under a single-step protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…[8] GagnØ and co-workers found that B(C 6 F 5 ) 3 promotes areductive cyclization of silyl-protected unsaturated polyols to give cyclopropanes and cyclopentanes depending on the substituents adjacent to the alkenyl moiety (Scheme 1c). [9] Unlike in our previous work, [8] GagnØ suggested as tepwise pathway involving an intramolecular attack of an eighboring alkenyl group at the activated CÀObond of the silaoxonium ion. This pathway takes advantage of anchimeric assistance [10] to generate abenzylic cation with C À Cbond formation.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…[8] GagnØ and co-workers found that B(C 6 F 5 ) 3 promotes areductive cyclization of silyl-protected unsaturated polyols to give cyclopropanes and cyclopentanes depending on the substituents adjacent to the alkenyl moiety (Scheme 1c). [9] Unlike in our previous work, [8] GagnØ suggested as tepwise pathway involving an intramolecular attack of an eighboring alkenyl group at the activated CÀObond of the silaoxonium ion. This pathway takes advantage of anchimeric assistance [10] to generate abenzylic cation with C À Cbond formation.…”
mentioning
confidence: 55%
“…Based on the selectivity and precedent in previous reports, [8,9] threec yclization pathways can be proposed (Scheme 2): 1) an S N 2'-type concerted mechanism (path A), 2) stepwise cyclobutanation (path B), and 3) as tepwise ringclosing and ring-expansion cascade (path C). All three possible pathways are assumed to be initiated by the formation of as ilaoxonium ion complexed with borohydride (I).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…next studied the borane‐catalyzed deoxygenation of unsaturated cyclic polyols. A series of silyl‐protected glycals were subjected to 8 ‐promoted hydrosilylation conditions [ 8 (10 mol %), Et 3 SiH (3.5 equiv), −40–25 °C] to provide the corresponding triols in yields of 62–88 %; the allylic moiety had a Z configuration with 83–98 % selectivity (Scheme ) …”
Section: Hydrosilylative Ring Opening Of Sugarsmentioning
confidence: 99%
“…As eries of silyl-protected glycals were subjected to 8-promotedh ydrosilylation conditions [8 (10 mol %), Et 3 SiH (3.5 equiv), À40-25 8C] to provide the corresponding triols in yields of 62-88 %; the allylic moiety hadaZ configurationw ith 83-98 %selectivity (Scheme 37). [54] The reactionp athway fort he reduction of glycals was assumed to proceed through consecutivea llylic reductions with high selectivity: the first allylic reduction took place at the C3 positiont hrough an S N 2' (C1) mechanism to form a2 ,3-disubsituted-3,6-dihydro-2H-pyran,a nd the second CÀOb ond cleav-age, leading to ring opening, occurred at C1 through an S N 2 pathway.I nterestingly,t he resulting triols contained two triethylsilyl protecting groups at the O5 and O6 positions, in addition to one parentO -trimethylsilyl group at O4, which indicated that 8 mediated chemoselective silyl group exchange that involved ad isilaoxonium speciesw ith ab orohydridea nion (Scheme 38).…”
Section: Hydrosilylative Ring Opening Of Sugarsmentioning
confidence: 99%
“…[11] De novo synthesis is also proposed as an alternative method for the synthesis of deoxy sugars, [13] but suffers from multistep synthesis,l ow yield, and low availability of starting materials.Recently,GagnØ and co-workers demonstrated an effective method for selective breaking of CÀOb onds in silyl-protected polyols,u sing B(C 6 F 5 ) 3 and at ertiary silane,t od eliver chiral polyol synthons while maintaining the stereocenters of polyols. [14][15][16] However,t he method required silyl protection of the OH groups and more than an equivalent amount of silane additives.T herefore, catalytic and selective transformation of sugars,w ithout protection of the OH groups,t og ive deoxy sugars while maintaining the original stereochemistry and using cheap reductants,such as H 2 ,isideal.…”
mentioning
confidence: 99%